Development and application of metal contacts on polycrystalline diamond films using combination of HF and arc plasma sources - Muratov, R.M.; Vierovkin, A.A.; Kutny, V.E.; Nezovibat’ko, Yr.N.; Rybka, A.V.; Taran, V.S. (Вопросы атомной науки и техники, 2014)
In this paper, the technology of application of ohmic contacts using arc discharge assisted by HF field was developed for semiconductor radiation detectors production. Polycrystalline diamond material for production of detectors was synthesized by chemical vapor deposition method (CVD) in NSC KIPT. Bilayer contacts were deposited on polycrystalline CVD (pCVD) diamond films, where the first layer was chromium, and the second layer – copper or stainless steel respectively. Electro-physical characteristics of pCVD diamond detectors with different contact materials were studied. Представлена технология нанесения омических контактов с помощью дугового разряда с ассистирован-ным ВЧ-полем для полупроводниковых датчиков ионизирующего излучения. Поликристаллический алмазный материал для производства детекторов был синтезирован методом химического осаждения из газовой фазы (CVD) в ННЦ ХФТИ. Двухслойные контакты наносились на pCVD-алмазные пленки, первый слой состоял из хрома, а второй – из меди или нержавеющей стали соответственно. Исследованы электрофизические характеристики детекторов на основе поликристаллического алмаза с разным материалом контактов. Представлена технологія нанесення омічних контактів за допомогою дугового розряду з асистированим ВЧ-полем для напівпровідникових датчиків іонізуючого випромінювання. Полікристалічний алмазний матеріал для виробництва детекторів був синтезований методом хімічного осадження з парової фази (CVD) в ННЦ ХФТІ. Двошарові контакти наносилися на pCVD-алмазні плівки, перший шар був з хрому, а другий – з міді або нержавіючої сталі відповідно. Досліджено електрофізичні характеристики детекторів на основі полікристалічного алмазу з різним матеріалом контакту.